M1 and M2 macrophage recruitment during tendon regeneration induced by amniotic epithelial cell allotransplantation in ovine. (April 2016) - Mauro, Annunziata; Russo, Valentina; Di Marcantonio, Lisa; Berardinelli, Paolo; Martelli, Alessandra; Muttini, Aurelio; Mattioli, Mauro; Barboni, Barbara
Abstract: Recently, we have demonstrated that ovine amniotic epithelial cells (oAECs) allotransplanted into experimentally induced tendon lesions are able to stimulate tissue regeneration also by reducing leukocyte infiltration. Amongst leukocytes, macrophages (Mφ) M1 and M2 phenotype cells are known to mediate inflammatory and repairing processes, respectively. In this research it was investigated if, during tendon regeneration induced by AECs allotransplantation, M1Mφ and M2Mφ phenotype cells are recruited and differently distributed within the lesion site. Ovine AECs treated and untreated (Ctr) tendons were explanted at 7, 14, and 28 days and tissue microarchitecture was analyzed together with the distribution and quantification of leukocytes (CD45 positive), Mφ (CD68 pan positive), and M1Mφ (CD86, and IL12b ) and M2Mφ (CD206, YM1 and IL10 ) phenotype related markers. In oAEC transplanted tendons CD45 and CD68 positive cells were always reduced in the lesion site. At day 14, oAEC treated tendons began to recover their microarchitecture, contextually a reduction of M1Mφ markers, mainly distributed close to oAECs, and an increase of M2Mφ markers was evidenced. CD206 positive cells were distributed near the regenerating areas. At day 28 oAECs treated tendons acquired a healthy-like structure with a reduction of M2Mφ. Differently, Ctr tendons maintained a disorganized morphology throughout the experimental time and constantly showed high values of M1Mφ markers. These findings indicate that M2Mφ recruitment could be correlated to tendon regeneration induced by oAECs allotransplantation. Moreover, these results demonstrate oAECs immunomodulatory role also in vivo and support novel insights into their allogeneic use underlying the resolution of tendon fibrosis. Highlights: Investigation on M1 and M2 macrophages recruitment during tendon regeneration after oAECs allotransplantation in ovine Results evidence M1 towards M2 macrophage skew in oAEC treated tendons. Pro-regenerative M2 macrophages correlate with microarchitecture recovery in oAEC treated tendons. oAECs in vivo have an anti-inflammatory effect supporting their pro-regenerative potential. New insights are provided on macrophages involvement during oAECs tendon regeneration.